Ayurvedic Management of Alcohol Use Disorder - A Case Series (AYUSHDHARA, 2024)
Alcohol Use Disorder (AUD) is a medical condition characterized by impaired ability to stop or control alcohol use despite the adverse social, occupational, or health consequences which ranges from mild to severe. AUD includes symptoms of alcohol intoxication, withdrawal as well as dependence. Etiological perspective applies a bio psychosocial framework that emphasizes the interplay of genetics, neurobiology, psychology and individual’s societal context. Globally around 1.4% of the population have AUD and 3 million deaths result from harmful alcohol use each year. Contemporary management includes medical intervention, counselling, outpatient program, or a residential inpatient stay, but the relapse rate is high. Hence the medical world is focusing on indigenous medicine and its probable outcome in the management of AUD. Objectives: In Ayurveda, the context of Madatyaya refers to conditions resultant from improper and excessive usage of alcohol and even other substance use. Every patient is being examined thoroughly as per Ayurveda parameters and based on the observations as well as the severity; individualized protocols are being framed. The case series includes 4 cases of AUD which was managed with a protocol including withdrawal management with Nasya, Sirodhara as well as internal medicines. This was followed by Snehapana, Vamana or Virechana, therapeutic yoga, family counselling as well as administration of Rasayana so as to address the dependence. The treatment protocol was finalised as per the assessment of Doshas, based on the clinical presentation. The outcome was assessed with CIWA-Ar, AUDIT, and SADQ Questionnaire. Result: Such a protocol is capable of addressing the bio-psychosocial factors of AUD and was observed as effective. Symptomatic improvement was noticed after the treatment in all the four cases and there was improvement in scores of assessment. The result was promising as well.